An exploration into the awareness and perceptions of medical students of the psychosociocultural factors which influence the consultation: Implications for teaching and learning of health professionals - Paula Diab; Margaret Matthews (South African Medical Association, 2016)
Background. South African society is undergoing rapid changes, and includes people from different cultures, beliefs and social backgrounds. Research suggests that these contextual influences have an important bearing on how patients present and relate to healthcare providers. Medical students, too, have a life-world based on their own backgrounds and cultures, and may find relating to a patient with a different life-world challenging. Objectives. To explore students’ awareness and perceptions of how psychosociocultural factors in a multicultural society influence the consultation, and to suggest adaptations for teaching. Methods. Focus group discussions were conducted with final-year medical students in the Family Medicine rotation. Some of the students had viewed a video of a consultation with an isiZulu-speaking patient, and completed a self-reflection learning task. Audio recordings were transcribed and analysed thematically. Results. Exposure to patients in the clinical years had made students aware of the challenges of cultural diversity, although they felt under-prepared to deal with this. Students alluded to the influences of their own cultures, of cultural similarities as well as differences, the roles and behaviours of doctors and patients in cross-cultural consultations, the potential knowledge and experience gap that exists across cultures, and an awareness of the need for patient-centredness. Conclusion. Students should be assisted to improve their cultural competence. Recommendations are made for using various methods, including critical incidents and visual learning to provide opportunities for reflexive practice and transformative learning. Educators must be equipped to address learning objectives relating to cultural competence.